SOUTH KOREA’S SOFT POWER IN THE DRAMA SERIES “CRASH LANDING ON YOU”: PROPAGANDA AGAINST NORTH KOREA - Irianto, Gilang Pratama; Rachman, Junita Budi; Sylviasari, Deasy (Universitas Padjadjaran, 2024)
This article examines South Korean propaganda aimed at influencing the public towards North Korea through the military-themed drama series Crash Landing on You interspersed with romantic stories typical of Korean dramas. The propaganda techniques used in the drama use glorification and demonization techniques. The purpose of this paper is to analyze South Korean soft power propaganda in the drama series Crash Landing on You. Propaganda in international relations is used as an analytical tool in this study, as well as the meaning of propaganda and propaganda techniques as supporting concepts for this study. The method used is a qualitative method, observations are made by observing the contents of the drama. The type of data used in this study is secondary data in the form of document studies, and the validity of the data is obtained by observing the drama series which is the research instrument. Based on the results of the study, it is concluded that South Korea uses popular culture as propaganda which contains elements of glorification and demonization. Korean dramas are the most easily accepted media and are easier to influence public perception. So through the drama series Crash Landing on You as a propaganda medium and wrapped in romantic stories, which have a significant influence in shaping public opinion about North Korea as a “backward” country and creating a positive image of South Korea. The broadcast of the drama had a negative impact on North Korea because the public increasingly viewed North Korea negatively as a country with a cruel dictator leader. This certainly benefited South Korea because the drama series was quite popular, but it also harmed North Korea because the country’s image became worse in the eyes of the world. So from this propaganda, the relationship between the two countries became heated.